Strategi Pengembangan Komoditi Alam untuk Peningkatan Pendapatan Penduduk Lokal di Desa Sumber Agung Kec. Keluang Kab. Muba - Mansyur, Imam (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
This community service examines the impact of the implementation of KKN in Sumber Agung Village, Keluang District, Musi Banyuasin Regency, with a focus on education and local resource-based economic development. Through a qualitative descriptive approach, it identifies the challenges faced by the community, such as limited educational facilities, lack of diversification of agricultural products, and low utilization of agricultural waste to increase economic value. To overcome these problems, namely by strengthening the economic skills of the community and student participation in village social activities. One of the leading programs is training in processing local agricultural products, such as kepok bananas, sweet potatoes, and cassava into high-value products, such as chips and other snacks. In addition, students introduce the innovation of utilizing palm oil fronds as raw materials for environmentally friendly plates to replace single-use plastic. This program aims to increase public understanding of economic opportunities based on available natural resources and encourage the creation of sustainable small businesses. The results of the activities show an increase in community skills in managing local products and an increase in awareness of the importance of innovation in small businesses. The community becomes more skilled in producing banana chips and environmentally friendly plates that have the potential to increase household income. In addition, students actively participate in various village social activities, such as attending cooperative meetings, participating in youth activities, and interacting with community leaders. This involvement strengthens students' social relationships with residents and enriches students' understanding of rural social dynamics.